Explorers in Eden : Pueblo Indians and the promised land - Auerbach, Jerold S. (University of New Mexico Press, 2006)
Beginning in the late nineteenth century, the pueblos of the Southwest frequently inspired Anglo-American visitors to express their sense of wonder and enchantment in biblical references. Frank Hamilton Cushing's first account of Zuni pueblo described a setting that looked like 'The Pools of Palestine'. Drawn to the Southwest, Mabel Dodge imagined "a garden of Eden, inhabited by an unfallen tribe of men and women." There she was attracted to Tony Luhan, a Taos Indian who looked "like a Biblical figure." When historian Jerold Auerbach first saw Edward S Curtis's early twentieth-century photograph 'Taos Water Girls, ' he realised that "here, indeed, was the biblical Rebecca, relocated to New Mexico from ancient Haran, where Abraham's faithful servant had journeyed to find a suitable wife for Isaac. Rebecca with her water pitcher is as familiar a biblical icon as Noah and his ark or Moses with the stone tablets. Curtis had recast her as the archetypal Pueblo maiden." The book uncovers an intriguing array of diaries, letters, memoirs, photographs, paintings, postcards, advertisements, anthropological field studies, and scholarly monographs. They reveal how Anglo-Americans disenchanted with modern urban industrial society developed a deep and rich fascination with pueblo culture through their biblical associations